2012
DOI: 10.1177/1545109711423444
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Oral Candidal Carriage and Its Association with CD4 Count between HIV-Positive and Healthy Individuals

Abstract: Within the limits of the study, we concluded oral candidal carriage rate and density carriage higher in HIV-positive patients than in healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(23 reference statements)
2
6
0
Order By: Relevance
“…Kamtane et al . 30 , in 2003, verified salivary Candida spp in 15% of non-HIV-infected patients and 55% in HIV-infected patients. Other studies reported fungus colonization in HIV-positive patients between 44% and 62% 9,31-33 .…”
Section: Discussionmentioning
confidence: 96%
“…Kamtane et al . 30 , in 2003, verified salivary Candida spp in 15% of non-HIV-infected patients and 55% in HIV-infected patients. Other studies reported fungus colonization in HIV-positive patients between 44% and 62% 9,31-33 .…”
Section: Discussionmentioning
confidence: 96%
“…21 In our study, OCC was significantly higher in HIV + subjects compared with the HIV − population, a finding similar to those of previous studies. 16,20,[22][23][24][25][26][27][28] However, the commensal status ascribed to Candida species makes it mandatory that evaluation of carrier status be accompanied by quantification of the yeast population to determine the predictive value of OCC towards oral candidiasis. 19,29,30 The density carriage of Candida is reported to increase significantly in the progression from asymptomatic yeast carrier to an episode of oral candidiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Tenfold serial dilutions were carried out, and another aliquots of 50 μl were seeded on Sabouraud dextrose agar. Colony forming units (CFU) of Candida were counted after 48 hr of incubation at 37°C (Kamtane, Subramaniam, & Suvarna, 2013).…”
Section: Oral Candida Carriage Measurement and Candida Species Idenmentioning
confidence: 99%